Remediation of soil contaminated with decabrominated diphenyl ether using white rot fungi - Wu, Junqin; Zhao, Yuechun; Lie, Lu; Fan, Biao; Li, Minghua (Journal of Environmental Engineering and Landscape Management, 2013)
Biodegradation of decabrominated diphenyl ether (BDE-209) in soil by white rot fungi under various experimental conditions was investigated in this study. It was found that BDE-209 in soil could be rapidly and efficiently degraded by white rot fungi, and the biodegradation fits the pseudo-first-order kinetics during a 15-day incubation period. The residues of BDE-209 in soil decreased with the increased amount of white rot fungi addition. It can be seen from the results that white rot fungi have a good degradation ability with one-step and two-step addition method. In native soil, the degradation of BDE-209 reached 52.65%, which was higher than that in sterilized soil. About 37.76–53.74% of BDE-209 degradation was observed in different soil types after 15 days. In addition, it was confirmed in this study that the presence of Cu2+, Cd2+ could enhance the remediation of soil contaminated with BDE-209, and the residues decreased by 69.20% and 54.65% for Cu2+ and Cd2+ treatment, respectively. However, the superior ability of white rot fungi to degrade BDE-209 was not obvious at low pollution level (<0.5 mg kg−1). First published online: 08 Feb 2013